Kehujjahan Hadis Mursal Perspektif Ibn Hazm - Faruq, Umar (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2023)
Mursal Hadith is narrated by old or small tabi’in to Prophet Muhammad Saw whether it is come from words, deeds or his decisions. Based on the definition, the status of mursal hadith as determined by hadith scholars is judge to be hadis d}a>if because the sanad of hadith is not connected to Prophet Muhammad (inqi}ta’) and the identity of narrator in the hadith is unknown (majhu>l). This research will try to answer the aunthenticity of the mursal hadits by mustasyaddid hadith scholar from Andalusia, namely Ibn H}azm. By using Library Research as the research method, it can be concluded that the criteria have been set by Ibn H}azm to determine the h}ujjah of mursal hadith does not accept hadith which is came from Ahl Madinah as h}ujjah. These criteria have implications especially for Ahl Madinah, Ibn H}azm automatically did not accept their hadis as h}ujjah even though his criticism was different from the other hadith scholar.